2019
DOI: 10.1111/pcmr.12828
|View full text |Cite
|
Sign up to set email alerts
|

Delineating the role of MITF isoforms in pigmentation and tissue homeostasis

Abstract: MITF, a gene that is mutated in familial melanoma and Waardenburg syndrome, encodes multiple isoforms expressed from alternative promoters that share common coding exons but have unique amino termini. It is not completely understood how these isoforms influence pigmentation in different tissues and how the expression of these independent isoforms of MITF is regulated. Here, we show that melanocytes express two isoforms of MITF, MITF‐A and MITF‐M. The expression of MITF‐A is partially regulated by a newly ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…Despite being detected in many cell lines, MITF-C is not found in cells of the melanocyte-lineage (Fuse et al, 1999). in RPE and iris (Flesher et al, 2020). Surprisingly, both Mitf-M knockout mice and Mitf-A overexpressing mice showed enlarged kidneys (Flesher et al, 2020;Phelep et al, 2017).…”
Section: Ta B L E 2 Summary Of Mouse Mitf Isoformsmentioning
confidence: 97%
See 3 more Smart Citations
“…Despite being detected in many cell lines, MITF-C is not found in cells of the melanocyte-lineage (Fuse et al, 1999). in RPE and iris (Flesher et al, 2020). Surprisingly, both Mitf-M knockout mice and Mitf-A overexpressing mice showed enlarged kidneys (Flesher et al, 2020;Phelep et al, 2017).…”
Section: Ta B L E 2 Summary Of Mouse Mitf Isoformsmentioning
confidence: 97%
“…The functional role of the different MITF isoforms has not been fully investigated. Isoform‐specific knockouts showed that mice lacking Mitf‐M do not have melanocytes in the epidermis, hair follicle, iris, and choroid, whereas there was no change of pigmentation in RPE and iris (Flesher et al., 2020). Surprisingly, both Mitf‐M knockout mice and Mitf‐A overexpressing mice showed enlarged kidneys (Flesher et al., 2020; Phelep et al., 2017).…”
Section: Mit‐tfe Isoformsmentioning
confidence: 99%
See 2 more Smart Citations
“…Briefly, the relative quantity and distribution of melanocyte products, such as eumelanin and pheomelanin, determine the fur color [4,5]. It has been reported that gene expression affects the pigmentation of rabbit fur through various mechanisms; for example, some genes, such as SLC7A11 [6][7][8], melanocortin receptor 1 (MC1R) [9][10][11], microphthalmia-associated transcription factor (MITF) [12], and ASIP [13], are likely to influence the production and deposition of melanin.…”
Section: Introductionmentioning
confidence: 99%